PROTOTIPE PENJEJAK 3 SUMBU PADA UJI STATIS WAHANA MENGGUNAKAN ARDUINO UNO - Ficri Arrasyid; Rahmat Ramdhani; Munnik Hariyanti (JURNAL TEKNOLOGI INDUSTRI, 2020)
Tracker is one of the tools found at the Ground Control Station (GCS). GCS itself can be interpreted as an aircraft control station, quadcopter, Unmanned Aerial Vehicle (UAV), or other flying objects operating on the earth's surface, either on land or on ships.In tracking operation, a control device is needed to control the servo movement. operate the tracker using the MPU6050 Sensor as a servo motor control to follow changes in the angular speed of the object, and the GPS module GY-GPS6MV2 to determine the position of the object's coordinates.The average MPU6050 sensor reading at 0 ° is 1.35 ° for x angle, -0.92 ° for y angle, and 0.22 ° for z angle. The average reading for 30 ° is 30.61 ° for x angle, 29.83 ° for y angle, and 30.11 for z angle. The mean reading at 45 ° is 45.34 ° for x angle, 45.33 ° for y angle, and 45.08 ° for z angle. The average reading for 60 ° is 60.90 ° for x angle, 60.62 ° for y angle, and 60.07 for z angle. The average reading at 90 ° is 90.86 ° for x angle, 90.37 ° y angle, and 90.25 ° z angle. meters with the closest error distance of 0.24 meters and the farthest error distance is 3.82 meters. With an average acceptance time of 14.48s. Keywords: Global Positioning System (GPS), MPU 6050, Ground Control Station (GCS).